Mineração e unidades de conservação no Amapá: possibilidades e riscos - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
The State of Amapá has a history marked by the activity of mining, whether it is prospecting or industrial mining. The mining activity, in turn, is not only accompanied by development and good results, it is also responsible for major environmental and social impacts. Interests conflict on the many existing protected areas in Amapá, considered the best preserved state of Brazil, with 70,31% of protect areas. The stand-off between mining and conservation areas is more evident, in view of the fact that the locational rigidity of mineral resources does not allow free choice of local exploration and extraction. More recently, from the debates about sustainability, society began to wonder about the socio-environmental costs of mining. Thus, the present study aimed to verify the possibility of mining in protected areas in Amapá, as well as the risks arising from the activity. Data were collected from publications of previous studies on mining and consultation to the current legislation. For demonstrating the potential and mineral interest in the Conservation Units, maps were prepared in ArcGIS 9.2. The Capivara area of panning, in Amapá National Forest, was discussed as a case study regarding the impacts. The sustained and proven hypothesis is that there is legal provision for mining in protected areas, however, there are risks related to the activity that must be taken into consideration
Keywords: Mineração; Unidade de conservação; Recursos minerais; Extração mineral; Degradação ambiental; Amapá (Estado); CNPQ::CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOLOGIA::MINERALOGIA